Slip of the tongue - Danh Vo 1975-; Ault, Julie 1957-; Bourgeois, Caroline 1959-; Knes, Heinz Peter 1969-; Pedersen, Stefan A. (Marsilio, 2015)
A pictorial book presenting an operation set out to create an artistic short-circuit. Danh Vo's conceptual artworks and installations often draw upon elements of personal lived experience (his own, the lives of his parents and other family members) to explore broader historical, social or political themes, particularly those relating to the history of Vietnam at the close of the twentieth century. The works showing in this book—closely related to an exhibition at the Pinault Foundation in Venice—in addition to Vo's site-specific installations, include some curious old works of art from Venetian museums and collections, provocatively chosen by Vo to establish an unprecedented dialogue between past and present